Small core FBG-based temperature compensated 'smart' contact lens for effective intraocular pressure measurement. (December 2019) - Chen, Ye; Wang, Jun; Zhao, Yin; Liu, Xiao-Jun; Zhang, Hong; Murdoch, Ian; Hull, Chris; Barbur, John; Sun, Tong; Grattan, KennethT.V.
Abstract: In this work, a small core, Fibre Bragg Grating (FBG)-based smart contact lens for intraocular pressure (IOP) measurement has been demonstrated. Further, an integral temperature compensation mechanism has been developed and included in the sensor design, allowing it to offer good long-term measurement capability while allowing for any local temperature fluctuations. The sensitivity of the device has been shown to be 12.9 p.m./mmHg, yielding good repeatability in tests carried out. Such a small core fibre, FBG-based smart contact lens shows significant potential for improving the management and therapy of glaucoma, the second most common cause of preventable blindness in the world.